Determinants of food security among rural households in Magong, Northwest Province, South Africa - Sentsho, Segametse Christina (My University, 2020)
Food security is a broad concept especially as far as rural food security in countries is concerned. In essence, it is a phenomenon with the goal of ensuring that all individuals have at all times, an adequate level of food and which they will be able to utilize to meet their increasing consumption demand. Studies have shown that like other countries, South Africa is food secure at the national level but very food insecure at the household level. It is also shown that food insecurity is not fuelled by a lack of food but a lack of food insecurity tackling strategies. The aim of the study is to examine the determinants of food security among rural households in Magong, North West Province, South Africa where the main prevalent economic activity is farming supported with other formal and informal types of employment. A multi-stage sampling technique was used to select the respondents that were interviewed. The first stage involved selecting districts and the second stage was the selection of municipalities. Farm and non-farming households were selected. Structured questionnaire were administered to 108 households. The third stage involved a selection Magong village using purposive sampling based on high concentration of both farming and non-farming activities were selected, which in our case is Magong. The fourth stage involved the selection of respondents based on simple random sampling proportionate to size. The study employed logit model for as data analysis. Of the variables modelled, only income and land size had a significant influence on food security. As far as age is concerned, it was evident that the youth participation in agriculture lacks. This is because most young people are still after white collar jobs. Some were still in the academic world awaiting their certificates which they hope to use a ticket to their first job. The participation in agriculture increases steadily between ages 31 and 50 which could be because the persons in this age brackets were looking for ways to store their wealth as they approach their retirement age. Some of the respondents have inherited the farms from family members and are therefore “forced” to keep the family business running for the sake of sustainability. With regards to the marital status, there is a high number of single/ never married respondents compared to the other groups. This could be people co-habiting and choosing not to marry as a result of the economic conditions making marriage costs unaffordable. Divorce was at its lowest amongst the respondents.v In terms of the gender of the respondents, there was a high participation of women in agriculture. This may be a result of women-based agricultural programmes implemented in the past in the study area. All the variables had a positive relationship with food security. Age had a positive effect of food security, with a positive parameter (β=0.013) which indicated that contrary to what other researchers found, an increase in age when all other factors are held constant, resulted in an increase in food security. The marital status of the household head also positively affected food security. This indicated that compared to their unmarried counterparts, married household heads were food secure (β=0.049). The findings also indicated that married couples and people living with partner had a higher chance of being food secure than those who were single, divorced or widowed. According to the results, male headship of households increases food security by 0.398. It was found that the larger the household size, the more food secure it is. This may be because as the number of members in the household increase, they find more ways of making money and combating food insecurity. A unit increase in household size increases food security by .093 while an increase in land size, increases food security by 0.394. This is expected because as the land size increases, there are chances that the productivity will also increase. From the results of the survey household income had a positive effect on food security. Income is very important as it determines the household’s affordability and its ability to meet its needs
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2020
Keywords: Determinants of food security; Rural households; Magon; Magong; NorthWest Province; South Africa; Food security; Food security -- Climatic factors; Food supply -- South Africa -- North West